- Kanker Prostat, Diagnosis Dini, dan Faktor Prognostik di Indonesia : Tinjauan Literatur: Tinjauan Literatur - Mochammadin, Rafly Abdullah; -, Intanri Kurniati; -, Ramadhana komala; Fitria Saftarina (CV. Jasa Sukses Abadi, 2024)
Prostate cancer is one of the most common types of cancer among men, with a significantly increasing prevalence worldwide, including Indonesia. Early diagnosis of prostate cancer is critical to improving patient survival, and PSA (Prostate-Specific Antigen) serves as a key biomarker in this process. Elevated PSA levels are often an early indicator of prostate cancer, although many men are unaware of the symptoms in the early stages, which can lead to a late diagnosis. Therefore, regular screening of PSA levels is highly recommended, especially for men over the age of 50 years. This study evaluated the role of PSA in the diagnosis of prostate cancer as well as prognostic factors affecting patient survival. Results showed that high PSA levels were associated with the likelihood of prostate cancer, and factors such as the number of metastatic lesions and the patient's general health condition had a significant influence on clinical outcomes. Education about the symptoms and risks of prostate cancer needs to be improved to encourage men to undergo regular health checks. With a better understanding of prostate cancer and an appropriate